Surface electromyography based method for computing muscle strength and fatigue of biceps brachii muscle and its clinical implementation. (2018) - Kuthe, Chetan D.; Uddanwadiker, Rashmi V.; Ramteke, Alankar A.
Abstract: Introduction: The main objective of the present study is to compute muscle strength in terms of muscle force and fatigue for biceps brachii, using trained and untrained subjects in static contraction (isometric contraction). Methods: There are two groups of 14 subjects each as trained subjects and untrained subjects. An isometric contraction is performed by two groups at three submaximal contraction levels L1 (50% MVC), L2 (75% MVC) and L3 (100% MVC) for 60 s each or until task failure, whichever comes first. The study compared the strength of the two groups based on maximal isometric muscle force and state of muscle fatigue using the slope of median frequency (MDF). Results: It was found that there was an 18.39% increase in the biceps brachii muscle strength for trained subjects as compared with untrained ( P  < 0.05), and the difference in the value of MDF between trained and untrained subjects was 1.36% at L1, 3.48% at L2 and 6.17% at L3. The untrained group showed a more negative slope (−0.2470) as compared to the trained group (−0.2155). Clinical implementation: The proposed method is clinically validated on total knee replaced patients with their consent. Conclusions: The method is used to monitor the muscle strength and for prognosis of muscle fatigue in isometric contraction.